Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Basmar Travelindo Sejahtera - Yolanda Kris; Achmad Syahlani (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
PT Basmar Travelindo Sejahtera is a tourism company engaged in Umrah and international travel services, operating under official PPIU and government permits. The company’s vision is to become a leading and trusted Umrah tour provider that prioritizes service quality and customer satisfaction. This study aims to analyze the simultaneous influence of the work environment and work discipline on employee performance at PT Basmar Travelindo Sejahtera. The population and sample in this study consist of all 30 employees. A quantitative descriptive approach was used, with data analyzed using IBM SPSS Version 25. The results of the partial hypothesis test show that the work environment has a positive and significant influence on employee performance, as indicated by a t-count value of 2.223 greater than the t-table value of 2.051, with a significance of 0.035 (<0.05). This finding means that the better the work environment, the higher the employee performance. The work discipline variable also shows a positive and significant influence on performance, with a t-count value of 2.157 greater than the t-table value of 2.051 and a significance of 0.040 (<0.05). The simultaneous hypothesis test produces a significance value of 0.000 (<0.05), indicating that both the work environment and work discipline together have a significant and positive effect on employee performance. These results highlight the importance of supportive work conditions and consistent discipline in improving performance at PT Basmar Travelindo Sejahtera.